(untitled) (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2025)
The present study was conducted to assess the Cardiovascular Response To 12 Weeks Aerobic Training in College Male Students. The objective of the study was to find out the effect of 30 minutes continuous aerobic workout on Resting Heart Rate (RHR) of sedentary male subjects for a total duration of twelve weeks. For the purpose of the study, Forty (n=40) male subjects were selected. The age group of the subjects ranged from 18 years to 24 years. The statistical technique employed for analysing the data were mean, standard deviation and ‘t’ test. The level of significance was set at 0.05 levels for interpreting the results. The result of the study indicates a significant difference in Resting Heart Rate (RHR) between continuous aerobic training group and control group. Further, continuous aerobic training group had significantly higher average performance mean score as a result of twelve weeks of aerobic training than the control group subjects who were not engaged in any training programme.